SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA MENGGUNAKAN METODE PROFILE MATCHING PADA SMA NEGERI 6 KOTA JAMBI: Scholarship, Profile Matching, Student - Rini, Faiza; -, Makmunsyah (JURNAL AKADEMIKA, 2019)
Public Senior High School 6 is a school located in the city of Jambi, each semester this school distributes scholarships to students. Scholarships distributed by schools are to help disadvantaged students. The problems faced by state Senior High School 6 in the selection of scholarships have not only been on target and the selection process has not been effective so that the scholarships given are uneven. Inaccuracies in selecting scholarships often occur, because the selection team is carried out by teachers from their own schools. Teachers who become the selection team only have little time to do the selection process besides having to teach. to overcome this problem, the research method that will be used is the profile matching method. Because profile matching uses accurate calculations and can be calculated the truth. So that this research can be recommended so that the selection of scholarship selection in Senior High School 6 is more selective.